2023
DOI: 10.1007/s11661-023-07005-z
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature Corrosion of ~ 30 Pct Porous FeCr Stainless Steels in Air: Long-Term Evaluation Up to Breakaway

Abstract: In this work, a long-term (up to 6000 hours) corrosion evaluation of three porous (~ 30 pct of initial porosity) ferritic iron-chromium alloys with different Cr contents (20, 22, and 27 wt pct of Cr) was carried out at 600 °C, 700 °C, 800 °C, and 900 °C in air. Mass gain measurements and SEM analyses revealed that at temperatures above 600 °C, all alloys exhibit breakaway corrosion, whereas at 600 °C, none of the alloys were heavily oxidized even after 6000 hours. Based on the results, the diffusion character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…However, the porous 430L alloy used in this study did not seem to agree with the conclusions of Tucker et al As shown in Figure 9, although the oxide scale thickness reached about 3 µm at about 300 h, no breakaway oxidation was observed in the micro-morphology (shown in Figures 3-8), and therefore 3 µm cannot be directly used as the failure criterion for the metal-supported SOFC stainless steel substrate in the present experiment. Furthermore, we cannot rule out the feasibility of such a standard due to variations in sintering temperatures, porosities, and oxidation conditions among different alloys [41].…”
Section: Oxide Thickness and Substrate Life Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the porous 430L alloy used in this study did not seem to agree with the conclusions of Tucker et al As shown in Figure 9, although the oxide scale thickness reached about 3 µm at about 300 h, no breakaway oxidation was observed in the micro-morphology (shown in Figures 3-8), and therefore 3 µm cannot be directly used as the failure criterion for the metal-supported SOFC stainless steel substrate in the present experiment. Furthermore, we cannot rule out the feasibility of such a standard due to variations in sintering temperatures, porosities, and oxidation conditions among different alloys [41].…”
Section: Oxide Thickness and Substrate Life Analysismentioning
confidence: 99%
“…Koszelow et al investigated the service life of ferrites at different temperatures. They predicted the service life of Fe27Cr in the air at 700 • C to be in the range of 5070 (±2740 h) [20,41,42]. For the porous 430L (~16 wt.% Cr) stainless steel, the weight increase ranges from 1.85 to 2.77 wt.% if all the chromium forms Cr 2 O 3 , and approximately 2.46 to 3.69 wt.% if all the chromium forms Fe/MnCr 2 O 4 spinel.…”
Section: Oxide Thickness and Substrate Life Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate original Cr content (i.e. an abundant Cr reservoir) is a necessary condition for the long life of the alloy [ 13 ]. The element diffusion and oxidation kinetics of steel matrix during the long-term working process are usually positively dependent on temperature [ [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%